(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the prevalence and characteristics of sleep disorders among adults aged 18-60 years residing in two communes, wards of Thai Binh province during the period 2024-2025. Subjects and methods: A cross-sectional descriptive study was conducted to assess the status of sleep disorders among 1760 adults aged 18-60 living in Tran Lam ward (Thai Binh city) and Thuy Duyen commune (Thai Thuy district), Thai Binh province, from August 2024 to January 2025. Results: The prevalence of sleep disorders among adults was 24.2%, with a higher rate observed in females than in males. Insomnia was the most common disorder (23.5%), followed by nightmares (4.8%) and restless legs syndrome (4.2%). Among nocturnal symptoms, nighttime awakening was the most frequent (92%), followed by hypnic jerks (39%) and feeling excessively cold during sleep (34.7%). Conclusion: Sleep disorders are common among adults aged 18-60 years, with a higher prevalence in females.